(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article discusses the opinion of researchers in the field of international trade operations over the countries, methods of payment export and import operations, experience and practice in the development of international trade in developed countries. Factors stimulating their development and obstacles hindering the development of international trade operations also have been identified in Uzbekistan.